Effects of Diffusion Layer (DL) and ORR Catalyst (M-ORR) on the Performance of M-ORR/IrO2/DL Electrodes for PEM-Type Unitized Regenerative Fuel Cells - Choe, Seunghoe; Lee, Byung-Seok; Jang, Jong Hyun (KOREAN ELECTROCHEMISTRY SOC, 2017)
This study aims to examine the influences of substrates/diffusion layers (DL) and oxygen reduction reaction catalysts (M-ORR) on the performance of M-ORR/IrO2/DL-type bifunctional oxygen electrodes for use in polymer electrolyte membrane (PEM)-type unitized regenerative fuel cells (URFC). The M-ORR/IrO2/DL electrodes were prepared via two sequential steps: anodic electrodeposition of IrO2 on various DLs and fabrication of M-ORR layers (Pt, Pd, and Pt-Ru) by spraying on IrO2/DL. Experiments using different DLs, with Pt as the M-ORR, revealed that the roughness factor of the DL mainly determined the electrode performance for both water electrolyzer (WE) and fuel cell (FC) operations, while the contributions of porosity and substrate material were insignificant. When Pt-Ru was utilized as the M-ORR instead of Pt, WE performance was enhanced and the electrode performance was assessed by analyzing round-trip efficiencies (epsilon(RT)) at current densities of 0.2 and 0.4 A/cm(2). As a result, using Pt-Ru instead of Pt alone provided better epsilon(RT) at both current densities, while Pd resulted in very low epsilon(RT). Improved efficiency was related to the additional catalytic action by Ru toward ORR during WE operation.
Keywords: ELECTROCATALYST; OPTIMIZATION; EFFICIENCY; CORROSION; DESIGN